EFEITO DO VINHOTO E CANA DE AÇÚCAR NA VIABILIDADE DE ADULTOS DE Stomoxys calcitrans (DIPTERA: MUSCIDAE) - Silva, Otávia Reis e (2014)
ABSTRACT. Silva O.R., Andriotti P.A. & Bittencourt A.J. [Vinasse and sugar cane effect in Stomoxys calcitrans (Diptera: Muscidae) adults emergence.] Efeito do vinhoto e cana de açúcar na viabilidade de adultos de Stomoxys calcitrans (Diptera: Muscidae). Revista Brasileira de Medicina Veterinária, 35(Supl.2):61-67, 2013. Departamento de Medicina e Cirurgia Veterinária, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, Campus Seropédica, BR 465, Km 7, Seropédica, RJ 23897-970, Brasil. E-mail: bittenc@ufrrj.br Eggs from Stomoxys calcitrans flies were maintained in diets prepared with sugarcane and 3 different levels of vinasse; the emergence of adults, their viability, and the development period from eggs to adults were evaluate in these different diets. Groups of 50 eggs each (with 4 repetitions) were incubated in climate chambers at 27ºC and 80% RH. Groups of 25 eggs each (with 3 repetitions) were maintained at room temperature in the laboratory bench (27±1ºC and RH 70-80%). Eggs were held in diets prepared with crushed sugarcane and vinasse, in different proportions as follows: group I) 1 Kg sugarcane plus 500 mL vinasse; group II) 1 Kg sugarcane plus 1 L vinasse; group III) 1 Kg sugarcane plus 2 L vinasse. Control groups (absence of vinasse) were prepared for each diet with distilled water and sugarcane. It was observed a better development of the eggs into adults in the diets with low amounts of vinasse; accordingly, in the diets with higher amounts of vinasse, the emergence of adult flies was reduced. The development period from egg to adult varied from 11 to 14 days. In the groups with more vinasse, flies emergence period was longer (14 days) without, however, producing more adults. In the groups with lower concentration of vinasse, the adult emergence period was shorter (12 to 13 days), and more adults were obtained from eggs. Fungal contamination was observed in the diets of the groups that were incubated in climate chambers; this contamination was not observed in the groups held at room temperature on the laboratory bench. Groups left on the bench yielded better results in comparison with groups incubated in climate chambers, once viability of bench groups were always more elevated (52% in group II). Associating the results of adult emergence with the amount of available substrate, it is possible to suggest that there is a potential for 1,000 to 13,000 adult emergencies of flies per ton of straw produced in the mechanical harvesting of sugarcane. These numbers can be increased 10 times since for each hectare of sugarcane harvested, 10 tons of straw are left on the ground. Vinasse associated with sugarcane might assist in the development of S. calcitrans adults, as it keeps the moisture of the material and facilitates fermentation of what remains on the soil after sugarcane harvesting, making it more attractive for the stable fly development. This condition may lead to the appearance of outbreaks in a few generations of flies due to the amount of substrate available and the large expanse of land occupied by sugarcane culture.